The translational termination signal database. - Brown, C M (1993)
The Translational Termination Database (TransTerm) consists of the immediate context sequences around the natural termination codons from 45 organisms, and summary tables. The influence of termination codon context on their effectivness as stop signals has been widely documented. The SPECIES--TRI.DAT table shows trinucleotide stop codon usage in each organism and for comparison the occurrence of these sequences in the noncoding region. The SPECIES--TETRA.DAT table contains is a similar table of tetranucleotide stop signal usage. The database is available from EMBL.